Tf2NH-catalyzed 1,6-conjugate addition of vinyl azides with p-quinone methides: a mild and efficient method for the synthesis of β-bis-arylamides - Rathod, Jayant; Sharma, Brijesh M.; Mali, Pramod S.; Kumar, Pradeep (Synthesis, 2017)
Tf2NH-catalyzed tandem 1,6-conjugate addition/Schmidt type rearrangement using vinyl azides and p-quinone methides to access a variety of β-bis-arylated amides is reported. The method is quick, efficient, mild, and high yielding with broad substrate scope.